KOMBINASI ELEKTROKOAGULASI DAN OKSIDASI LANJUT BERBASIS O3/GAC DALAM MENGOLAH LIMBAH INDUSTRI BATIK - Debora Rousyella Saulina Tampubolon; Firra Rosariawari (EnviroUS, 2021)
The use of chemical dyes in the batik-making process causes the batik industrial waste to contain pollutants that are difficult to decompose. In addition, the levels of COD and TSS of batik industrial waste are also high. The combination of electrocoagulation and advanced oxidation based on O3 / GAC in batch or continuously aims as an alternative technology and to determine the effect of electrode distance, detention time, ozone dose, and sampling time on the efficiency of COD, TSS removal, and the color of batik industrial waste. With a variation of the electrode distance of 2 cm, 4 cm, 6 cm; detention time 20 minutes, 40 minutes, 60 minutes, 80 minutes, 100 minutes; ozone dose 0.25 g O3 / L; 0.5 gr O3 / L; 0.75 gr O3 / L; and sampling times of 30 minutes, 60 minutes, 90 minutes, 120 minutes, 150 minutes, the best results were obtained for COD, TSS, and color, respectively 110.4 mg / L; 40 mg / L; 30 PtCo in batch systems and 552 mg / L; 360 mg / L; 374 PtCo on a continuous system. Keywords: Electrocoagulation, Advanced oxydation process based O3/GAC, Batik industrial waste